Lessons from Iceland: developing scalable and sustainable community approaches for the prevention of mental disorders in young Australians - E Hoare; IE Thorisdóttir; AL Kristjansson; ID Sigfusdóttir; Josh Hayward; Steven Allender; Claudia Strugnell; N Reavley; G Patton; Michael Berk; Felice Jacka (2019)
Adolescence is the primary age of onset for common psychiatric disorders and thus presents a singular opportunity for prevention, particularly in school settings. Research efforts have advanced the understanding of diverse and interacting risk and protective factors for anxiety and depression. Such factors span individual, family, school, economic, cultural, biological, and other domains. Despite this, Australian prevention programs have largely limited their focus to individual-level protective skills through psychoeducation, such as resilience and relationship building, usually with modest and short-term positive effects. We propose that multi-disciplinary, systems and community-based prevention efforts are needed to account for the complexity in underlying factors that contribute to common mental disorder onset. The Icelandic Model of Prevention, which has been shown to reduce substance use among adolescents, holds valuable insights for the prevention of other common mental disorders among Australian youth as it involves strengthening coordination within communities to reduce multiple risk factors and promote multiple protective factors. Effective prevention of depression and anxiety disorders, which arise as a result of multiple complex risk factors, is also likely to require structurally embedded, systems and community-based approaches to develop and implement local action that incorporates, and is adaptive to, context.